Rh(III)-Catalyzed, Redox-Neutral, C–H Multifluoroalkenylation of Benzamides - Lin, Wei; Qu, Yifei; Zhu, Huixuan; Xie, Mei; Hu, Jinhui; Xiong, Zhuang; Chen, Wen-Hua; Xu, Jun; Wu, Jia-Qiang (Synthesis, 2024)
Fluorinated molecules are widely used in pharmaceutical and agrochemical industries. Multifluoroalkyl-containing compounds have attracted increasing attention for their unique ability to alter the activity of drugs and bioactive molecules. Herein, we report an efficient Rh(III)-catalyzed, redox-neutral, C–H multifluoroalkenylation of benzamides with multifluoroalkenes, which provides a versatile protocol for accessing a wide range of multifluoroalkenylated arenes.
Keywords: C–H activation; rhodium; multifluoroalkenylation; benzamide; redox-neutral